The Changing of Parental Communication Mode in Building Children Motivation Career (Jurnal Bimbingan dan Konseling Islam, 2022)
Change does not always have a negative impact on the living system, there are positive values ??that can always be learned from a change. In social communication, for example, individuals and groups have a stake in making choices about communication methods. This paper specifically describes how changes in parental communication modes in building children's career motivation. In this paper, the method used is a qualitative descriptive method where the technique is a literature study data collection technique, namely looking for relevant literature on online news pages on the internet. Content analysis is used by reading and interpreting data to describe how changes in parental communication modes with children affect children's career motivation. The findings in this paper show that changes in technology-based communication modes in building motivation provide space for children to represent their desires in the career field. In addition, parents in this case also provide positive feedback on children's choices, so as to create healthy relationships that can make children feel accepted and heard within the family and community